2023
DOI: 10.1017/s0950268823001735
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of incomplete childhood hepatitis B vaccination in Sierra Leone, Liberia, and Guinea: Analysis of national surveys (2018–2020)

George A. Yendewa,
Peter B. James,
Amir Mohareb
et al.

Abstract: Vaccination against hepatitis B virus (HBV) is effective at preventing vertical transmission. Sierra Leone, Liberia, and Guinea are hyperendemic West African countries; yet, childhood vaccination coverage is suboptimal, and the determinants of incomplete vaccination are poorly understood. We analyzed national survey data (2018–2020) of children aged 4–35 months to assess complete HBV vaccination (receiving 3 doses of the pentavalent vaccine) and incomplete vaccination (receiving <3 doses). Statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
3
0
0
Order By: Relevance
“…Furthermore, it was noteworthy that being Muslim was a predictor of COVID-19 vaccine hesitancy in our study. This observation aligns with prior reports both from and outside Sub-Saharan Africa, which document increased levels of vaccine hesitancy among Muslim communities in the context of COVID-19 and other infectious diseases [18,[25][26][27]. For instance, we observed in a recent study that children of Muslim parents had lower odds of completing the hepatitis B vaccination series for infants in Sierra Leone and Guinea, two countries with majority Muslim populations [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, it was noteworthy that being Muslim was a predictor of COVID-19 vaccine hesitancy in our study. This observation aligns with prior reports both from and outside Sub-Saharan Africa, which document increased levels of vaccine hesitancy among Muslim communities in the context of COVID-19 and other infectious diseases [18,[25][26][27]. For instance, we observed in a recent study that children of Muslim parents had lower odds of completing the hepatitis B vaccination series for infants in Sierra Leone and Guinea, two countries with majority Muslim populations [27].…”
Section: Discussionsupporting
confidence: 92%
“…This observation aligns with prior reports both from and outside Sub-Saharan Africa, which document increased levels of vaccine hesitancy among Muslim communities in the context of COVID-19 and other infectious diseases [18,[25][26][27]. For instance, we observed in a recent study that children of Muslim parents had lower odds of completing the hepatitis B vaccination series for infants in Sierra Leone and Guinea, two countries with majority Muslim populations [27]. Similarly, a recent systematic review and meta-analysis conducted in the United Kingdom noted that being a Muslim parent was associated with decision making regarding routine childhood vaccinations [28].…”
Section: Discussionsupporting
confidence: 91%
“…11 Another study looking at childhood vaccination in Sierra Leone, Liberia and Guinea found that children of Muslim mothers were less likely than Christian mothers to complete Hepatitis B vaccination. 9 This is consistent with a recent study on immunisation in Sierra Leone, which saw a higher likelihood of missed vaccination for children with Muslim caregivers compared to children with Christian caregivers. 26 While these findings might not be consistent with all Muslims, it is believed that vaccine hesitancy and rejection among Muslims might be connected to whether vaccines are 'halal' (religiously permissible) or in line with Islamic teachings, particularly during the month of Ramadan.…”
Section: Cummings Et Al (2023) Conducted a Study On Vaccine Uptake Am...supporting
confidence: 91%